Application Of Augmented Reality In Learning Bakery For Autism Spectrum Disorder - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Suparjoh, Suriawati; Muhamad Khidir, Nur Alya Sahira (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Many young children with ASD have difficulty learning the language spoken. Some kids can use just single words while others can create sounds. Someone else couldn't talk at all. Communication is a vital skill in life that contributes to improved interactions and quality of life. Researchers think it's difficult for all young children who have communication impairments to generate and maintain a mental representation in conjunction with the instant fact, that building capabilities are critical. A child with ASD can be taught to interact in numerous distinct ways. For example, a child can study to use the sign language, exchange objects or images and use a voice output electronic device. All these methods of communication are efficient and useful, but we would also like to teach the child to interact with the language spoken. The questionnaire has been distributed to the target user who is a special education teachers from PEMATA for user acceptance testing. Each respondent runs individual tests after the developer provides a brief explanation of the application. They need to scan and test the augmented reality applications on recipe book.